The effect of comparison of brown sugar and sugar drying time on the quality of jerkey banana heart (musa paradisiaca l) - Chairil Anwar; Irmayanti Irmayanti (Journal Of Agritech Science (JASc), 2022)
This study aims to measure and identify quantitatively and qualitatively on the quality of banana heart beef jerky. This study used a factorial Completely Randomized Design (CRD) with 2 factors studied, namely the ratio of brown sugar and granulated sugar (G) and drying time (P), each of which consisted of 3 levels, namely the ratio of brown sugar and granulated sugar consisting of G1 : (30 grams: 30 grams), G2: (20 grams: 40 grams) and G3: (40 grams: 20 grams). Sun drying time (P) consisted of P1 : 3 days, P1 : 4 days, and P3 : 5 days. Comparison of brown sugar and granulated sugar had a very significant effect (P 0.01) on the water content, but not significant (P > 0.05) on the organoleptic value of aroma, taste, color and texture of banana heart beef jerky. Drying time had no significant effect (P > 0.05) on the moisture content and organoleptic value of aroma, taste, color and texture of banana heart beef jerky. The interaction of the ratio of brown sugar and granulated sugar and drying time had no significant effect (P > 0.05) on the moisture content and organoleptic values ​​of aroma, taste, color and texture of banana heart beef jerky. The best banana flower jerky was obtained from the treatment with a ratio of brown sugar and granulated sugar 1:1 (30gram: 30 gram) (G1) and drying time of 3 days (P1) with an analysis of 10.10% moisture content, 3.87 color (like), taste 3.90 (like), aroma 3.63 (neutral), texture 3.70 (like), fiber content 2.97%.